Soydans ikke-Breivik og Højgaards ikke-ikke-Breivik: 22. juli i et dokumentarteaterperspektiv - Böhnisch, Siemke (Peripeti, 2014)
In this article I discuss and analyse two highly contested documentary performances, Manifest 2083 (Lollike/CaféTeateret, 2012) and Breiviks Erklärung (Rau/IIPM, 2012), which are based on text documents by the mass murderer and terrorist Anders Behring Breivik. The analysis focuses on questions of enunciation and the embodiment practices of the two solo actors, Sascha Ö. Soydan in Breiviks Erklärung and Olaf Højgaard in Manifest 2083.